Clinical and genetic analysis of a case series of 12 Chinese families with hereditary ataxia - Guo, Liqi; Wu, Fangrui; Wang, Yuxi; Xiong, Xiaoping; Zhong, Min (Frontiers in Neurology, 2025)
Background and objectiveHereditary ataxia (HA) encompasses a diverse group of neurological disorders characterized by significant clinical and genetic heterogeneity. This case series study aims to present a case series of HA from Southwest China, thereby expanding the clinical and genetic understanding of the condition.MethodsA comprehensive review of medical records was conducted for patients with progressive ataxia who were evaluated at the Children’s Hospital of Chongqing Medical University and Qianjiang Central Hospital. The clinical manifestations, pedigree analysis, neuroimaging, and laboratory evaluations of the probands were systematically examined. Comprehensive genetic testing was conducted on peripheral venous blood samples to investigate HA.ResultsThe genetic analyses identified spinocerebellar ataxia (SCA) in six families, ataxia-telangiectasia in three families, ataxia with vitamin E deficiency in one family, ATP1A3-associated ataxia in one family, and SPTBN2-associated ataxia in one family. Further subtyping of SCA revealed the presence of SCA types 1, 2, and 3 among the patients. The participants were enrolled an average of 8.5 years after symptom onset, with the age of onset ranging from 1 to 50 years. Gait instability was the most prevalent clinical feature observed in our cohort.ConclusionWe identified 12 families with HA, including four genetic mutations that have not been previously documented. SCA3 was the most frequently inherited dominant ataxia, followed by ataxia-telangiectasia. Whole-exome sequencing has significantly increased the diagnostic yield in patients with suspected genetic ataxia and should be considered for all individuals with negative repeat expansion testing.